2014
DOI: 10.3389/fimmu.2014.00293
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antigen-Specific T-Cells as Immune Therapy for Chronic Infectious Diseases and Cancer

Abstract: T-cell responses are induced by antigen presenting cells (APC) and signals from the microenvironment. Antigen persistence and inflammatory microenvironments in chronic infections and cancer can induce a tolerant state in T-cells resulting in hyporesponsiveness, loss of effector function, and weak biochemical signaling patterns in response to antigen stimulation. Although the mechanisms of T-cell tolerance induced in chronic infection and cancer may differ from those involved in tolerance to self-antigen, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Harnessing the ability of DCs to induce Ag-specific CD8 + T cell immunity via cross-presentation is required for development of effective vaccines or therapies against many infectious diseases and cancer. 65,66 Our data suggests that LGO may possess the ability to enhance DC ability to induce OVA-specific CD8 + T cell activation (Fig. 6B, C and 7A).…”
Section: Discussionmentioning
confidence: 69%
“…Harnessing the ability of DCs to induce Ag-specific CD8 + T cell immunity via cross-presentation is required for development of effective vaccines or therapies against many infectious diseases and cancer. 65,66 Our data suggests that LGO may possess the ability to enhance DC ability to induce OVA-specific CD8 + T cell activation (Fig. 6B, C and 7A).…”
Section: Discussionmentioning
confidence: 69%
“…IL‐2 is a key mediator of apoptosis in peripheral autoreactive T cells, which play an essential role in maintaining self‐tolerance by CD4+CD25+ T regulatory (T reg) cells. Furthermore, some studies have indicated that IL‐2 is the main inducer of suppressive T reg cell production, suggesting that IL‐2 could be used therapeutically to treat several diseases, such as autoimmune diseases, neoplasias, and infectious diseases . Moreover, IL‐2 is essential for stimulating NK cell growth and differentiation to eliminate tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some studies have indicated that IL-2 is the main inducer of suppressive T reg cell production, suggesting that IL-2 could be used therapeutically to treat several diseases, such as autoimmune diseases, neoplasias, and infectious diseases. [44,45] Moreover, IL-2 is essential for stimulating NK cell growth and differentiation to eliminate tumour cells. IL-2 has been used for the treatment of melanoma and renal carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…2,24,25 A number of immunosuppressive mechanisms have been proposed. These include: spontaneous apoptosis of circulating T cells, 26,27 poor expression of co-stimulatory molecules and loss of HLA class I molecules on tumor cell surface, 28,29 a decrease in the absolute cell counts of specific T cell subsets, 30,31 predominant Th2 responses, [31][32][33][34] production of immunosuppressive factors by tumors, [35][36][37] T cell exhaustion, 38 over-expression of regulatory T cells and dysfunctional/inhibitory dendritic cells. 35,39 Earlier publications from our group and others have reported reduced levels of CD3f-chain in both tumor infiltrating lymphocytes and peripheral blood lymphocytes probably due to inhibitory factors, transcriptional defects and production of Arginase I in the tumor microenvironment by myeloid cells.…”
Section: Discussionmentioning
confidence: 99%